Internet of Things Applications, Challenges and Related Future Technologies - Kaur, Amandeep (Gyan Management Journal, 2020)
Nowadays Internet of Things (IoT) gained a great attention from researchers, since it becomes an  important technology  that promises  a  smart  human  being  life, by  allowing a  communications  between objects, machines and  every things  together with peoples. Io Trepresents  a system which  consists a things in the real world, and sensors attached to or combined to these things, connected to the   Internet via  wired  and wireless  network  structure.  The  IoT  sensors  can use  various  types  of  connections such as RFID, Wi-Fi, Bluetooth, and ZigBee, in addition to allowing wide area connectivity  using many technologies  such as GSM, GPRS, 3G,  and LTE. IoT-enabled things  will share  information  about  the condition  of things  and the  surrounding environment  with people, software systems and  other machines. by the technology of the IoT, the world will becomes smart in every aspects, since the  IoT will provides  a means of smart cities, smart healthcare, smart homes and building, in addition to  many important applications such as smart  energy, grid, transportation, waste management and  monitoring . In this paper we review a concept of many IoT applications and future possibilities for new  related technologies in addition to the challenges that facing the implementation of the IoT.
Keywords: IoT Applications; Future Technologies; Smart Cities; Smart Environment; Smart Energy and Grid; Smart Manufacturing.